Synthesis and Structures of Fe(II), Zn(II) and Pd(II) Complexes With a Schiff Base Derived from Methyl 2-Amino-6-Methyl-4,5,6,7-Tetrahydrothieno[2,3-c] Pyridine-3-Carboxylate and Comparison of Their Optical Constants for Different Solvents and Molarities - Turan Özerk, Nevin; Buldurun, Kenan; Gündüz, Bayram; Colak N. (American Scientific Publishers, 2017)
Schiff base derived from condensation of o-vanillin (3-methoxysalicylaldehyde) and methyl 2-amino-6-methyl- 4,5,6,7-tetrahydrothieno[2,3-c]pyridine-3-carboxylate and its metal complexes are synthesized and characterized based on elemental analyses, IR, 1H NMR, 13C NMR, magnetic susceptibility, mass spectra, UV-vis and thermal analysis (TGA). Specifically the spectral measurements display the octahedral structures of Fe(II), Zn(II) complexes and square planar geometry of Pd(II) complex. Here, the effects on optical constants such as absorbance, molar extinction coefficient, mass extinction coefficients, transmittance, absorption band edge and optical band gap of Fe(II), Zn(II) and Pd(II) complexes of the different solvents (dichloromethane (DCM), acetone and ethyl alcohol (EtOH)) and molarities (0.498, 0.249 and 0.124 mM) are investigated by solution technique. Copyright © 2017 by American Scientific Publishers All rights reserved.
Keywords: Absorption; Carboxylate Ligand; Electrical Sensing; Optical Band Gap; Palladium; Structure Educidation